Analisis Sistem Premi Panen Kelapa Sawit Terhadap Kinerja dan Kepuasan Kerja Karyawan (Studi Kasus: Unit Kebun Rambutan Perkebunan Nusantara III Kecamatan Paya Bagas) - Fitra Aristia Fahmi Lubis; Siti Mardiana; Mitra Musika Lubis (Jurnal Agriuma, 2021)
This research was conducted on September – October 2019 at Rambutan Plantation unit PT. Perkebunan Nusantara III, PayaBagas Sub-District, Serdang Bedagai District. The location of this research determined purposively and the sampling technic in this research was proportionate stratified random sampling with a total of 38 samples from cast section (Afdeling). From the results of the research conduded that the harvest salary system in PT. Perkebunan Nusantara III Rambutan Plantation were a task bare system determined based on the area topography and potential production. Harvest salaries significantly affect the performance (quality of work, quantity of work, work attendance) in the PT. Perkebunan Nusantara III Rambutan Plantation Unit.